PREVENTION OF CHILDHOOD STUNTING PROBLEMS WITH THE MAYANG–WATI PROGRAM - Linita Caesar Sasmita (Universitas Airlangga, 2021)
Stunting is a chronic nutritional problem that is being faced both nationally and globally. Stunting is a condition when a child being too short for his age or has a z–score of –2 SD (Standard Deviation). The impact of stunting can affect child development, cognitive abilities, and even cause mortality. The incidence of stunting is a priority problem that occurs in Mayangrejo Village, Kalitidu District, Bojonegoro Regency with a case prevalence of 21%. Community service activities carried out aim to provide recommendations for solutions in solving health problems that occur. The community service method is carried out sequentially starting from data collection activities, problem identification, problem priority determination, identification of the root causes of the problem, preparation of a Plan of Action (PoA), and implementation of interventions. Mayangrejo Berdaya Melawan Stunting (Mayang–Wati) Program is a recommended solution to solving stunting problems in Mayangrejo Village. The Mayang–Wati program consists of activities on Motivation of Pregnant Women, Seminars and Training on Making Weaning Food, Education on Reproductive Health, and Production of Health Information Media. Every activity in the Mayang–Wati program has different activity targets and can meet every success indicator set. The main objective of the Mayang–Wati program is to increase the knowledge and awareness of the residents of Mayangrejo Village towards the problem of stunting so that it can help reduce the prevalence of stunting. Suggestions from community service activities are that the Mayang–Wati program can be continued by village officials such as posyandu cadres and can become a proposal for activities for the Ponkesdes Mayangrejo. The sustainability of this program is important because it aims to create changes in the behavior of local villagers that cannot occur in a short time only during the implementation of community service.